(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The act of taking someone else’s property without permission not only causes material losses, but also disrupts ethical values ​​and social order. This article aims to examine this act from two legal perspectives: first, the perspective of Islamic law based on the hadith narrated by Muslim No. 2564, and second, the provisions of Indonesian positive law through Article 362 of the Criminal Code. In the hadith, a person’s blood, property, and honor are forbidden for other people who are Muslim. Meanwhile, Article 362 of the Criminal Code explains that taking someone else’s property with the intention of owning it unlawfully is a criminal act of theft. This study uses a literature study or. The results of the analysis show that both legal systems, both Islamic and national, view the act of taking someone else’s rights as a serious violation that must be subject to legal sanctions. Both legal views also emphasize the importance of integrity, a sense of responsibility, and respect for the ownership of others in maintaining social harmony.